On film editing an introduction to the art of film construction - Dmytryk, Edward 1908-1999 (Routledge, 2018)
In On Film Editing, director Edward Dmytryk explains, in clear and engaging terms, the principles of film editing. Using examples and anecdotes from almost five decades in the film industry, Dmytrykoffers a masterclass in film and video editing. Written in an informal, "how-to-do-it" style, Dmytryk shares his expertise and experience in film editing in a precise and philosophical way, contending that all parties on the film crew-from the camera assistant to the producer and director-must understand film editing to produce a truly polished work. Originally published in 1984, this reissue of Dmytryk's classic editing book includes a new critical introduction by Andrew Lund, as well as chapter lessons, discussion questions, andexercises
Keywords: Motion pictures / Editing